Price formation in Indian gold market: Analysing the role of gold Exchange Traded Funds (ETFs) against spot and futures markets. Issue 1 (March 2020) - Kaur, Prabhdeep; Singh, Jaspal
Abstract: The paper examines the relative efficiency of gold Exchange Traded Funds (ETF) against spot gold and gold futures in the Indian scenario, using a series of conventional and threshold cointegration statistics. The results reveal that gold ETFs and spot gold, as well as gold ETFs and gold futures, converge together in the long run. Also, movements in spot prices and futures prices are found to lead those in ETF prices, thus, providing scope for executing profitable trading strategies in ETFs. The study further explores the probable reasons that might account for the relative inefficiency observed in ETF prices.